Comparison of Enoxaparin and Rivaroxaban in the Prophylaxis of Deep Venous Thrombosis in Arthroplasty - Necati Çiçek; İsmail Ağir; Hacı Bayram Tosun; Abuzer Uludağ; Abdulkadir Sari (Emergency Medicine International)
Background. Pulmonary embolism is a serious early complication of arthroplasty procedures that can develop after deep venous thrombosis. The present study aimed to compare rivaroxaban and enoxaparin in terms of preventing DV and PE, and also in this study, we compared the complications due to these drugs in patients undergoing elective arthroplasty. Materials and Methods. 214 patients were divided into three groups based on their treatment regimens. In group I, enoxaparin was used, in group II, rivaroxaban was used, and in group III, enoxaparin was used throughout hospitalization, and after hospital discharge, rivaroxaban was used. These three groups were compared according to the occurrence of deep venous thrombosis, pulmonary embolism, and major and minor complications. Results. Major postoperative complications occurred in 5, 15, and 6 patients in group I, II, and III, respectively. Minor postoperative complications occurred in 10, 24, and 11 patients in group I, II, and III, respectively. No significant difference was found among the three groups. Deep venous thrombosis or pulmonary embolism was not observed in any patient. Conclusion. Rivaroxaban was found to be as effective as enoxaparin in the prevention of deep venous thrombosis and other complications after arthroplasty. Moreover, oral rivaroxaban provided greater ease of use compared to subcutaneous enoxaparin. Based on these findings, we consider that rivaroxaban could be an effective alternative to enoxaparin.